Role of Adjuvant Treatment in Sinonasal Mucosal Melanoma - Amit, Moran; Tam, Samantha; Abdelmeguid, Ahmed S.; Kupferman, Michael E.; Su, Shirley Y.; Raza, Shaan M.; DeMonte, Franco; Hanna, Ehab Y. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Purpose Sinonasal mucosal melanoma (SNMM) is a locally aggressive tumor. This study aimed to define the role of adjuvant treatment and its association with survival outcomes of SNMM.Methods This retrospective study investigated 152 patients with SNMM treated between 1991 and 2016 in MD Anderson Cancer Center. Patients were divided into the following treatment groups: surgery alone, surgery with postoperative radiotherapy (PORT), surgery with postoperative chemoradiation (POCRT), and induction chemotherapy followed by surgery and PORT. Overall survival (OS), disease-specific survival, and relapse-free survival were compared. Survival between the groups was compared using univariate and multivariate analyses.Results The median follow-up was 28 months (range: 2–220 months). Five-year OS rates were 39, 42, 47, and 27% for the surgery only, PORT, POCRT, and neoadjuvant chemotherapy groups, respectively (log rank p = 0.73). Distant metastasis was the most common form of treatment failure and occurred in 59 (39%) patients. Five-year distant metastasis rates were 51, 45, and 58% for patients treated with surgery alone, PORT, and POCRT, respectively (log rank p = 0.21) but unable to be estimated in the neoadjuvant chemotherapy group due to low OS rates. Multivariate analysis demonstrated tumor site (hazard ratio [HR] = 2.32, 95% confidence interval [CI] = 1.24–4.15) and smoking status (HR = 1.77, 95% CI = 1.02–3.1) to be significant prognostic factors for survival.Conclusion Tumor site and smoking status were significant prognosticators in SNMM. A high rate of distant metastatic disease suggests that further investigation into novel, systemic therapies is required to improve outcomes in this disease entity.
Keywords: mucosal; melanoma; sinonasal; skull base; recurrence; chemotherapy; radiation; survival